1988
DOI: 10.1159/000266723
|View full text |Cite
|
Sign up to set email alerts
|

Cilioretinal Arteries in Large Optic Disks

Abstract: The cilioretinal arteries form a physiologic bypass between the ciliary and retinal circulation. The evaluation of photographs of 163 normal optic nerve heads revealed a significant (p < 0.001) correlation between the number of cilioretinal arteries and the optic disk and cup size: the larger the disk and cup the more vessels. The vessels’ prevalence in all optic disks was 27.0%. It increased from 0% in disks smaller than 2.00 mm2 to 50.0% in optic nerve heads larger than 4.1 mm2. No corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…Jonas et al 28 reported a prevalence of 27% in a study of 163 normal adult eyes with a preponderance in the temporal sector,27 identical to the results from our study. Jonas et al 28 also reported that optic nerves with a cilioretinal artery had a larger disc and may have a larger cup/disc ratio without pathology, again strongly in concordance with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Jonas et al 28 reported a prevalence of 27% in a study of 163 normal adult eyes with a preponderance in the temporal sector,27 identical to the results from our study. Jonas et al 28 also reported that optic nerves with a cilioretinal artery had a larger disc and may have a larger cup/disc ratio without pathology, again strongly in concordance with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Cilioretinal arteries form a physiological bypass between ciliary and retinal circulation and are reported to be present in 6–32% of the population 27 28. Jonas et al 28 reported a prevalence of 27% in a study of 163 normal adult eyes with a preponderance in the temporal sector,27 identical to the results from our study.…”
Section: Discussionsupporting
confidence: 87%
“…7.7%). This corresponds to a previous study where a significant correlation (p<0.001) between cilioretinal arteries and optic disc size was found: the smaller the disc the less cilioretinal arteries [6].…”
Section: Discussionsupporting
confidence: 91%
“…The morphology of the optic disc varies with its size. The variation in optic disc size is of morphogenetic importance, as eyes with large optic nerve heads, compared with those with small optic nerve heads, have (1) a larger neuroretinal rim area (Jonas et al 1988a), (2) more optic nerve fibers (Quigley et al 1991;Jonas et al 1992), (3) less nerve fiber per mm 2 disc area (Jonas et al 1992), (4) a higher count and a larger total area of lamina cribrosa pores (Jonas et al 1991), (5) a higher ratio of interpore connective tissue area to total lamina cribrosa area (Jonas et al 1991), (6) more cilioretinal arteries (Jonas et al 1988c) and (7) more retinal photoreceptors and retinal pigment epithelium cells in combination with a larger retinal surface area (Panda-Jonas et al 1994).…”
Section: Morphogenetic Importance Of Disc Sizementioning
confidence: 99%